You suck : a love story - Moore, Christopher, 1957- (New York : Harper, 2008)
New to San Francisco, nineteen-year-old Tommy is turned into a vampire by his sarcastic and sexy girlfriend, Jody, and the pair are hunted by Elijah, the elder who turned Jody, and the Animals, the stock boys with whom Tommy used to hang, who have deemed themselves vampire hunters.
Wilson's Fiction, March 2008
Library Journal Starred, December 2006
Pub Weekly, November 2006
Booklist, November 2006
Kirkus Review, November 2006
Adult
Keywords: Vampires -- Fiction; Vampires -- Fiction; Love stories; Humorous fiction; Love stories; Humorous fiction